Risk, Reward and Uncertainty in Buyer-Seller Transactions - The Seller's View on Combining Posted Prices and Auctions - - Radosveta Ivanova-Stenzel; Sabine Kröger (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
In Buy-It-Now auctions, sellers can post a take-it-or-leave-it price offer prior to an auction. While the literature almost exclusively looks at buyers in such combined mechanisms, the current paper summarizes results from the sellers' point of view. Buy-It-Now auctions are complex mechanisms and therefore quite challenging for sellers. The paper discusses the seller's curse, a bias that sellers might fall prey to in such combined mechanisms, and how experience counterbalances this bias. Furthermore, the paper explores the role of information and bargaining power on behavior and profit prospects in Buy-It-Now auctions.
Keywords: C72; C91; D44; D82; L1; 330; asymmetric information; laboratory experiment; field experiment; auction; BIN-auction; Buy-It-Now auction; BIN-price; Buy-It-Now price; combined mechanism